Hubungan Sistem Pengendalian Internal Pemerintah, Pemahaman Akuntansi dan Kualitas Laporan Keuangan - Elisabet Anjela Prabadianti; Teguh Erawati (Universitas Mataram, 2023)
This study aims to prove the effect of the government's internal control system, the use of information technology, the quality of human resources, and understanding of accounting on the quality of government financial reports. The sample in this study was the Regional Work Unit (SKPD) in West Cibal District, Manggarai Regency with a total of 60 respondents. The research sample was obtained by snowball sampling technique while data analysis was carried out by using multiple linear regression techniques.The results of this study prove that the government's internal control system affects the quality of financial reports, the use of information technology does not affect the quality of financial reports, the quality of human resources does not affect the quality of financial reports, and understanding of accounting affects the quality of financial reports.